Immunomodulatory effects of cysteamine and its potential use as a host-directed therapy for tuberculosis - Najafi-Fard, Saeid; Farroni, Chiara; Petrone, Linda; Altera, Anna Maria Gerarda; Salmi, Andrea; Vanini, Valentina; Cuzzi, Gilda; Alonzi, Tonino; Nicastri, Emanuele; Gualano, Gina; Palmieri, Fabrizio; Piacentini, Mauro; et al. (Frontiers in Immunology, 2024)
Objective: Cysteamine, a drug approved to treat cystinosis, has been proposed as a host-directed therapy for M. tuberculosis (Mtb) and SARS-CoV-2. The impact of cysteamine on the immune responses has not been fully investigated. We aimed to in vitro evaluate the immunomodulatory effects of cysteamine on peripheral blood mononuclear cells (PBMCs) using the purified protein derivative (PPD) as a recall antigen, and an unspecific stimulus as Staphylococcal Enterotoxin B (SEB). Methods: PBMCs isolated from subjects with tuberculosis infection (TBI), tuberculosis disease (TB), and healthy controls (HC), were in vitro stimulated with PPD or SEB, and treated or not with cysteamine at different concentrations (50-400 µM) for 6 hours (h) and 24h. We evaluated the T helper1 (Th1) and T cytotoxic1 (Tc1) cell cytokine production by flow cytometry and immuneenzymatic assays. In HC we also evaluated apoptosis and/or necrosis by flow cytometry.We observed an immunomodulatory effect of cysteamine at 400µM in PBMCs from TB and TBI subjects. It significantly reduced PPD-specific Th1 responses at 24h and at 6h (p=0.0004 and p=0.0009, respectively), and a similar non-significant trend was observed with cysteamine at 200µM (p=0.06 at 24h and p=0.14 at 6h). Moreover, cysteamine at both 400µM (p<0.0001 and p=0.0187 at 24h, respectively and p<0.0001 at 6h for both) and 200µM (p=0.0119 and p=0.0028 at 24h and p=0.0028 and p=0.0003 at 6h, respectively) significantly reduced SEB-induced Th1 and Tc1 responses. Further, we found that cysteamine induced morphological lymphocyte changes and significantly reduced the lymphocyte percentage in a dose-and time-dependent manner. Cysteamine at 400µM induced 8% late apoptosis and 1.6% necrosis (p<0.05) at 24h. In contrast, despite significant differences from untreated conditions (p<0.05), cysteamine at 400µM for 6h induced about 1% late apoptosis and 0.1% necrosis in the cells. Conclusions: High doses of cysteamine in vitro reduce the percentages of PPD-and SEB-induced Th1 and Tc1 cells and induce late apoptosis and necrosis. Differently, cysteamine at lower doses retains the immunomodulatory effect without affecting cell viability. These findings suggest cysteamine as a potential adjunct to antimicrobial regimens as in the TB or COVID-19 field, for its ability to reduce the inflammatory status.